PeachVar-DB: A Curated Collection of Genetic Variations for the Interactive Analysis of Peach Genome Data. (4th December 2017) - Cirilli, Marco; Flati, Tiziano; Gioiosa, Silvia; Tagliaferri, Ilario; Ciacciulli, Angelo; Gao, Zhongshan; Gattolin, Stefano; Geuna, Filippo; Maggi, Francesco; Bottoni, Paolo; Rossini, Laura; Bassi, Daniele; et al.
Abstract: Applying next-generation sequencing (NGS) technologies to species of agricultural interest has the potential to accelerate the understanding and exploration of genetic resources. The storage, availability and maintenance of huge quantities of NGS-generated data remains a major challenge. The PeachVar-DB portal, available at http://hpc-bioinformatics.cineca.it/peach, is an open-source catalog of genetic variants present in peach ( Prunus persica L. Batsch) and wild-related species of Prunus genera, annotated from 146 samples publicly released on the Sequence Read Archive (SRA). We designed a user-friendly web-based interface of the database, providing search tools to retrieve single nucleotide polymorphism (SNP) and InDel variants, along with useful statistics and information. PeachVar-DB results are linked to the Genome Database for Rosaceae (GDR) and the Phytozome database to allow easy access to other external useful plant-oriented resources. In order to extend the genetic diversity covered by the PeachVar-DB further, and to allow increasingly powerful comparative analysis, we will progressively integrate newly released data.